2004
DOI: 10.1101/gad.1245904
|View full text |Cite
|
Sign up to set email alerts
|

The geminivirus nuclear shuttle protein is a virulence factor that suppresses transmembrane receptor kinase activity

Abstract: Despite the large number of leucine-rich-repeat (LRR) receptor-like-kinases (RLKs) in plants and their conceptual relevance in signaling events, functional information is restricted to a few family members. Here we describe the characterization of new LRR-RLK family members as virulence targets of the geminivirus nuclear shuttle protein (NSP). NSP interacts specifically with three LRR-RLKs, NIK1, NIK2, and NIK3, through an 80-amino acid region that encompasses the kinase active site and A-loop. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
248
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(253 citation statements)
references
References 60 publications
(69 reference statements)
3
248
0
2
Order By: Relevance
“…BV1 in the DNA-B component of CaLCuV is located in a similar genomic locus as the bC1 gene of TYLCCNV/TYLCCNB (Cui et al, 2004;Fontes et al, 2004). Confocal microscopy experiments using BV1-CFP and At-MYC2-YFP showed that the two proteins colocalized in the nucleus (Supplemental Figure 8, fourth panel).…”
Section: Bc1 Interacts With the Myc2 Transcription Factor Of Plant Hostsmentioning
confidence: 98%
“…BV1 in the DNA-B component of CaLCuV is located in a similar genomic locus as the bC1 gene of TYLCCNV/TYLCCNB (Cui et al, 2004;Fontes et al, 2004). Confocal microscopy experiments using BV1-CFP and At-MYC2-YFP showed that the two proteins colocalized in the nucleus (Supplemental Figure 8, fourth panel).…”
Section: Bc1 Interacts With the Myc2 Transcription Factor Of Plant Hostsmentioning
confidence: 98%
“…This is achieved in part by modulating existing signal transduction pathways through the interaction of viral proteins and host protein kinases. Geminivirus proteins bind to RLKs that are part of the plant pathogen surveillance system and interfere with the ability of the host to mount a resistance response (Fontes et al, 2004). Susceptibility to geminivirus infection is also enhanced by interaction with an SnRK1, implicating this evolutionarily conserved, energy-sensing protein kinase in the plant defense response (Hao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Geminiviruses interact with both types of protein kinase signaling cascades to modulate host processes. The BR1 protein binds to three Leurich-repeat RLKs, NIK1, NIK2, and NIK2, to inhibit their kinase and antiviral activities (Fontes et al, 2004). In contrast, interaction and phosphorylation of BR1 by a PERK-like RLK, NsAK, is necessary for efficient infection and full symptom development (Florentino et al, 2006).…”
mentioning
confidence: 99%
“…Otros efectores virales actúan directamente sobre complejos PRRs. Es el caso de la proteína de transporte nuclear de los geminivirus que es capaz de interaccionar e inhibir la actividad quinasa de tres LRR-RLKs de Arabidopsis necesarias para la respuesta defensiva antiviral (Fontes et al 2004;Speth et al 2007). …”
Section: La Supresión De La Pti: Los Efectores Patogénicosunclassified